2021
DOI: 10.1097/md.0000000000025114
|View full text |Cite
|
Sign up to set email alerts
|

Statin/ezetimibe combination therapy vs statin monotherapy for carotid atherosclerotic plaque inflammation

Abstract: It remains uncertain whether statin/ezetimibe combination therapy serves as a useful and equivalent alternative to statin monotherapy for reducing atherosclerotic plaque inflammation. The aim of the present study was to compare the effects of statin/ezetimibe combination therapy and statin monotherapy on carotid atherosclerotic plaque inflammation using 18 F-fluorodeoxyglucose ( 18 FDG) positron emission tomography (PET)/computed tomography (CT) imaging. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our findings suggest that statin therapy, either alone or in combination with ezetimibe, significantly reduced carotid temperatures in those patients. This is in line with recent studies, where both statin monotherapy and the combination of ezetimibe with either simvastatin or rosuvastatin reduced FDG carotid wall uptake in patients with recent acute coronary syndrome [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that statin therapy, either alone or in combination with ezetimibe, significantly reduced carotid temperatures in those patients. This is in line with recent studies, where both statin monotherapy and the combination of ezetimibe with either simvastatin or rosuvastatin reduced FDG carotid wall uptake in patients with recent acute coronary syndrome [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although robust data exist about the impact of statin therapy on carotid wall inflammation [ 16 , 17 , 18 ], few data exist regarding the impact of ezetimibe on top of statin therapy on arterial wall inflammatory activation. In specific, the combination of ezetimibe with statin, compared to statin monotherapy, exerts a similar anti-inflammatory effect on carotid atherosclerotic plaque [ 14 , 15 ]. It is noteworthy that in a recent study the combination of ezetimibe with low-dose rosuvastatin showed inferior carotid wall anti-inflammatory effect compared to high-dose rosuvastatin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies following IMPROVE-IT have found that the benefits of concomitant ezetimibe and statin therapies were greatest in patients at high-risk of ASCVD ( 27 29 ). The ASCVD risk reduction seen with ezetimibe may not only be due to the LCL-C reduction, but also due to reduction of inflammation ( 30 ). Oh et al have revealed that an ezetimibe/statin regimen (ezetimibe 10 mg/simvastatin 10 mg and ezetimibe 10 mg/rosuvastatin 5 mg) reduces carotid atherosclerotic plaque inflammation to a similar extent compared to statin monotherapy (rosuvastatin 10 mg and rosuvastatin 20 mg) ( 30 ).…”
Section: Ezetimibementioning
confidence: 99%
“…The ASCVD risk reduction seen with ezetimibe may not only be due to the LCL-C reduction, but also due to reduction of inflammation ( 30 ). Oh et al have revealed that an ezetimibe/statin regimen (ezetimibe 10 mg/simvastatin 10 mg and ezetimibe 10 mg/rosuvastatin 5 mg) reduces carotid atherosclerotic plaque inflammation to a similar extent compared to statin monotherapy (rosuvastatin 10 mg and rosuvastatin 20 mg) ( 30 ). Masson et al support this finding by demonstrating the addition of ezetimibe to statin therapy led to a reduction of coronary atherosclerosis ( 31 ).…”
Section: Ezetimibementioning
confidence: 99%
“…Another study compared the effects of ezetimibe/statin combination therapy (ezetimibe/simvastatin 10 mg or ezetimibe/rosuvastatin 5 mg) and statin monotherapy (rosuvastatin 10 mg or 20 mg) on carotid atherosclerotic plaque inflammation in patients with mild carotid atherosclerosis and acute coronary syndrome (59). LDL-C levels were substantially and similarly reduced in both groups at follow-up, and atherosclerotic plaque inflammation of the carotid artery and aorta evaluated decreased similarly with both treatments, which suggests that an ezetimibe/statin combination therapy may provide anti-inflammatory effects comparable to statin monotherapy at equivalent LDL-C-lowering doses (59).…”
Section: Ezetimibe+bempedoic Acidmentioning
confidence: 99%